Implementation of Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) Methods in Decision Support Systems for Employee Performance Assessment at the Komite Olahraga Nasional Indonesia (KONI) DKI Jakarta: Implementasi Metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Penilaian Kinerja Pegawai di Komite Olahraga Nasional Indonesia (KONI) DKI Jakarta - Muhammad Dzakky Imaduddin Ikhwani; Anita Diana; Wendi Usino; Humisar Hasugian (Universitas Singaperbangsa Karawang, 2023)
This study describes the performance evaluation of top staff members of DKI Jakarta Komite Olahraga Nasional Indonesiasai (KONI). Evaluation of the best employees is important for facilitating system-based objective decisions for selecting the best employees. If you hire the wrong people, the selection thinking of the organization will not be objective, so it will not be a hiring mistake. Issues encountered include lack of evaluation criteria for each employee, no existing employee evaluation process, no employee evaluation process, no data report, no employee evaluation and ranking report for each employee, etc. there is. Criteria used include attendance, quotas, tardiness and working hours. Since the criteria need to be weighted, the Analytical Hierarchy Process (AHP) method is used. Use Method Simple Additive Weighting (SAW) to determine employee rankings for each criterion. The purpose of this study was to create a DSS with criteria and criteria to weight employee ratings and appraisals so that they could be assessed in more detail to review and share performance. reporting the results of employee evaluations. Under Employee Final Results (Ranking), you can see the ranking of each existing employee.